UNIT 29.17 Correlative Förster Resonance Electron Transfer‐Proximity Ligation Assay (FRET‐PLA) Technique for Studying Interactions Involving Membrane Proteins. (1st August 2016) - Ivanusic, Daniel; Denner, Joachim; Bannert, Norbert
Abstract : This unit provides a guide and detailed protocol for studying membrane protein‐protein interactions (PPI) using the acceptor‐sensitized Förster resonance electron transfer (FRET) method in combination with the proximity ligation assay (PLA). The protocol in this unit is focused on the preparation of FRET‐PLA samples and the detection of correlative FRET/PLA signals as well as on the analysis of FRET‐PLA data and interpretation of correlative results when using cyan fluorescent protein (CFP) as a FRET donor and yellow fluorescent protein (YFP) as a FRET acceptor. The correlative application of FRET and PLA combines two powerful tools for monitoring PPI, yielding results that are more reliable than with either technique alone. © 2016 by John Wiley & Sons, Inc.